Mechanism and prediction of multi-mode magnetic polaritons by MCLC circuit model in complex micro/nanostructures. (July 2021) - Guo, Yanming; Zhou, Sihong; Xiong, Bo; Shuai, Yong; Zhao, Junming
Highlights: Resonant frequency of the MP can be predicted by the proposed MCLC circuit model. The circuit of each mode is independent, when a multi-mode MP is excited. The excitation of a multi-mode MP is treated as the superposition of multiple single states/modes. Magnetic polariton coupling mode is tunable with geometric parameters. Combining MP dispersion relations, magnetic polariton coupling condition is reached. Abstract: Magnetic polariton (MP) which is the coupling of incident electromagnetic waves with nanostructures by excitation of artificial magnetic resonance has been widely applied in designing and tailoring wavelength-selective thermal radiative properties of micro/nanostructures. The equivalent inductor-capacitor (LC) circuit model is an effective method to explain and predict magnetic polaritons. However, the existing LC circuit model shows inaccurate MP predictions especially multi-mode MP in complex structures. To extend LC circuit model and explore the physical mechanism of MP, a multi-mode coupled LC (MCLC) circuit model with a multi-mode MP resonant condition is proposed in this work. The core ideas of MCLC mode are that when a multi-mode MP is excited, the circuit of each mode is independent of each other. The resonant frequency of each current circuit corresponds to a state that forms a resonance. The excitation of a multi-mode MP is treated as the superposition of multiple single states. The resonant frequency of the multi-mode MP amounts to the average effect of the superimposed states. MCLC circuit model shows better predictions on multi-mode MP resonant frequencies than the previous LC circuit model does in a double-layer strip array structure. Magnetic polariton coupling (MPC) can be well predicted and the MP coupling condition is reached. The rationality of MCLC circuit model is verified by comparing the predictions and calculations when geometric parameters are changed and the slits of double-layer strip array are filled with dielectric materials. No matter what media in slits are, the MP coupling condition is always applicable. This study may contribute to designing and predicting metamaterials based on MP and further MP physical mechanism researches.